2015
DOI: 10.3390/bios5040678
|View full text |Cite
|
Sign up to set email alerts
|

Bees as Biosensors: Chemosensory Ability, Honey Bee Monitoring Systems, and Emergent Sensor Technologies Derived from the Pollinator Syndrome

Abstract: This review focuses on critical milestones in the development path for the use of bees, mainly honey bees and bumble bees, as sentinels and biosensors. These keystone species comprise the most abundant pollinators of agro-ecosystems. Pollinating 70%–80% of flowering terrestrial plants, bees and other insects propel the reproduction and survival of plants and themselves, as well as improve the quantity and quality of seeds, nuts, and fruits that feed birds, wildlife, and us. Flowers provide insects with energy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 79 publications
(103 reference statements)
0
36
0
Order By: Relevance
“…A bioindication study (Ruschioni et al 2013) revealed that high levels of heavy metals are better detected in live than in dead bees. In addition, sampling with live bees presents other advantages over dead bees such as: (i) the sample size (number of bees to be sampled) can be selected without death restrictions; (ii) the age cohort of bees can be selected by sampling in different locations inside the hive (Van der Steen 2016); (iii) other hive-products (such as pollen) can be simultaneously sampled when using the appropriate traps; and (iv) the honeybee trail outside the hive can be tracked and even directed using modern micro-sensors and sound and chemical signals (Bromenshenk et al 2015).…”
mentioning
confidence: 99%
“…A bioindication study (Ruschioni et al 2013) revealed that high levels of heavy metals are better detected in live than in dead bees. In addition, sampling with live bees presents other advantages over dead bees such as: (i) the sample size (number of bees to be sampled) can be selected without death restrictions; (ii) the age cohort of bees can be selected by sampling in different locations inside the hive (Van der Steen 2016); (iii) other hive-products (such as pollen) can be simultaneously sampled when using the appropriate traps; and (iv) the honeybee trail outside the hive can be tracked and even directed using modern micro-sensors and sound and chemical signals (Bromenshenk et al 2015).…”
mentioning
confidence: 99%
“…have developed a system for automated continuous recording of sound emission by honeybees as a measure of their activity (Dietlein, 1985). The specific sounds from the hives are useful in providing information on colony behaviour, strength and health, and the data from the monitoring device can be accessed remotely from any internet-enabled device (Bromenshenk et al, 2015; Evans, 2015; Meikle and Holst, 2015). Other systems are being developed that integrate visual, acoustic and beehive monitoring systems and share them with the environmental monitoring platform (Figure 6).…”
Section: Biosensors For Animal Diseasesmentioning
confidence: 99%
“…Due to their complex biology (social life, reproduction, nutrition etc.) and intimate connection to climatic and vegetation conditions, honeybees are a natural biosensor of environmental quality [5][6][7][8][9]. Some of their special behaviors make honeybees a special pollinator: they exclusively feed on nectar and pollen; there is a high number of individuals in a colony, which leads to large quantities of food storage; they have the big ray of forage flight (0-5 km); their "flower fidelity" behavior makes them an efficient pollinator for a certain plant species at a certain moment; they visit many flowers based on the quality and quantity of nectar secretion; they have good orientation, memory and communication regarding food sources; they thermoregulate their nests, which helps overwintering; and they have the possibility to manage and transport their colonies to different crops.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of developing technologies based on electronic sensors combined with the Internet of Things (IoT) and big data storage, honeybees could become even better suited to be equipped and used to monitor different physical and biological aspects of their colonies in order to help beekeepers' management, to avoid high honeybee losses, and to understand the different environmental factors that are causing the declining of their species [9][10][11][12][13][14][15][16]. Thus, from the perspective of managing qualities and their sensitivity to environmental contaminants, the honeybee colony represents an important bio tool to understand and even quantify the impact of different aggressive factors that intersect with its complex social life.…”
Section: Introductionmentioning
confidence: 99%